Chemical Composition and Larvicidal Activity of the EssentialOil of Laurus nobilisL. from Iran: Essential oil of Laurus nobilis - Mohammadreza Verdian-Rizi (Iranian Journal of Pharmaceutical Sciences, 2009)
The chemical composition of the essential oil obtained from the aerial parts of Laurus nobilisL. has been examined by gas chromatography (GC) and GC- mass spectrometery (MS). The main components of the oil were identified. 1,8-Cineole was the major component in the oil together with ß-terpinyl acetate, terpinene-4-ol, α-pinene, ß-pinene, p-cymene, linalool and terpinene-4-ylacetate. The essential oil was tested against Anopheles stephensi and Culex pipienslarvae. The results obtained show that the essential oil could be considered as natural larvicidal agents.